Financial Inclusion, Financial Literacy, and Financial Technology Impact on the Sustainability of Micro, Small, and Medium Enterprises: A Study in the SMEs of Tidore Islands, Indonesia - Rinto Sahdan; Fitriani Sardju (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine how financial inclusion, financial literacy and financial technology affect the sustainability of micro, small and medium enterprises. The sample selection in this study used the Slovin formula. The data collection technique was carried out using a questionnaire, the object of this research was MSMEs in the City of Tidore Islands. Hypothesis testing in this study used Multiple Linear Regression Analysis with the help of SPSS. The results of this study found that: (1) financial inclusion affects the sustainability of MSMEs; (2) financial literacy affects the sustainability of MSMEs; (3) financial technology has no effect on the sustainability of MSMEs.